Musculotendinous Disorders in the Upper Extremity: Part 1. MRI of the Shoulder and Upper Arm - Fritz, Russell C.; Boutin, Robert D. (Seminars in Musculoskeletal Radiology, 2017)
Muscle and tendon injuries about the shoulder and upper arm are commonly evaluated and characterized with magnetic resonance imaging. This article reviews our experience with abnormalities of the rotator cuff tendons and muscles as well as the deltoid muscle in the shoulder. We discuss and illustrate abnormalities of the upper arm such as strain injuries of the pectoralis major, strain injuries of the teres major and latissimus dorsi, and contusion and crush injuries of the biceps and brachialis muscles in the upper arm.
Keywords: muscle; injury; sport; athlete; strain; shoulder; arm; MRI